TINGKAT MODERASI BERAGAMA DI KELURAHAN PANABARI HUTATONGA KECAMATAN TANO TOMBANGAN KABUPATEN TAPANULI SELATAN UNIVERSITAS ISLAM NEGERI SULTAN SYARIF KASIM - Marisa Hannum Harahap; Risnawati Risnawati; Miftahir Rizqa (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2023)
This study aims to see the existence of a level of religious moderation in Panabari Tano Tombangan Village in dealing with rampant radicalism and intolerance. This study reviews 4 indicators namely national commitment, non-violence, tolerance and accommodating local culture. The research used is quantitative, namely analyzing data quantitatively/statistically. Aims to analyze, describe, and obtain empirical evidence of the relationship between several variables.